Attitudes of Future Employees Towards Automation on the Example of Students of Cracow Universities - Janusz CZEKAJ; Dariusz FIRSZT; Marek JABLONSKI (Communications of International Proceedings, 2021)
The aim of the article is to diagnose the opinions of young people entering the labor market about the automation processes taking place in economy 4.0.  The study presents the results of empirical research conducted on a representative sample of students of Cracow universities. The choice of the place of the study resulted from the fact that Cracow is the location of numerous shared service centers, which are pioneers in the field of business process automation. The conducted research shows that the respondents are aware of what modern automation is all about and strongly assess its effects positively. They see the potential dangers of automation for the labor market, but they do not expect problems with finding a job after graduation, also in companies using automation.
Keywords: Automation; Labour Market; Economy 4.0